Characteristics and Prognosis of De Novo Hepatocellular Carcinoma After Sustained Virologic Response. Issue 7 (5th May 2021) - Toyoda, Hidenori; Hiraoka, Atsushi; Uojima, Haruki; Nozaki, Akito; Shimada, Noritomo; Takaguchi, Koichi; Abe, Hiroshi; Atsukawa, Masanori; Matsuura, Kentaro; Ishikawa, Toru; Mikami, Shigeru; Watanabe, Tsunamasa; et al.
Abstract : Hepatocellular carcinoma (HCC) can de novo develop in patients with chronic hepatitis C even after the achievement of sustained virologic response (SVR). We characterized de novo HCC after SVR, comparing it with HCC that developed in patients during persistent hepatitis C virus (HCV) infection. Characteristics, survival rates, and recurrence rates after curative treatment in 178 patients who developed initial HCC after SVR diagnosed between 2014 and 2020 were compared with those of 127 patients with initial HCC that developed during persistent HCV infection diagnosed between 2011 and 2015; HCC was detected under surveillance in both groups. HCC was less advanced and liver function worsened less in patients with SVR than in patients with persistent HCV. The survival rate after diagnosis was significantly higher for patients with SVR than for patients with persistent HCV (1‐, 3‐, and 5‐year survival rates, 98.2%, 92.5%, and 86.8% versus 89.5%, 74.7%, and 60.8%, respectively; P  < 0.001). By contrast, the recurrence rate after curative treatment was similar between groups (1‐, 3‐, and 5‐year recurrence rates, 11.6%, 54.6%, and 60.4% versus 24.0%, 46.7%, and 50.4%, respectively; P  = 0.7484). Liver function improved between initial HCC diagnosis and recurrence in patients with SVR ( P  = 0.0191), whereas it worsened in the control group ( P  < 0.001). In addition, patients with SVR could receive curative treatment for recurrence more frequently than patients with persistent HCV (80.4% versus 47.8%, respectively; P  = 0.0008). Conclusion: Survival of patients with de novo HCC after SVR was significantly higher than that of patients in whom HCC developed during persistent HCV infection, despite similar rates of recurrence after curative treatment. A higher prevalence of curative treatment for recurrent HCC and improved liver function contributed to this result. Abstract : image